Parthenolide Relieves Pain and Promotes M2 Microglia/Macrophage Polarization in Rat Model of Neuropathy. (18th May 2015) - Popiolek-Barczyk, Katarzyna; Kolosowska, Natalia; Piotrowska, Anna; Makuch, Wioletta; Rojewska, Ewelina; Jurga, Agnieszka M.; Pilat, Dominika; Mika, Joanna
Abstract : Neuropathic pain treatment remains a challenge because pathomechanism is not fully understood. It is believed that glial activation and increased spinal nociceptive factors are crucial for neuropathy. We investigated the effect of parthenolide (PTL) on the chronic constriction injury to the sciatic nerve (CCI)-induced neuropathy in rat. We analyzed spinal changes in glial markers and M1 and M2 polarization factors, as well as intracellular signaling pathways. PTL (5  µ g; i.t. ) was preemptively and then daily administered for 7 days after CCI. PTL attenuated the allodynia and hyperalgesia and increased the protein level of IBA1 (a microglial/macrophage marker) but did not change GFAP (an astrocyte marker) on day 7 after CCI. PTL reduced the protein level of M1 (IL-1 β, IL-18, and iNOS) and enhanced M2 (IL-10, TIMP1) factors. In addition, it downregulated the phosphorylated form of NF- κ B, p38MAPK, and ERK1/2 protein level and upregulated STAT3. In primary microglial cell culture we have shown that IL-1 β, IL-18, iNOS, IL-6, IL-10, and TIMP1 are of microglial origin. Summing up, PTL directly or indirectly attenuates neuropathy symptoms and promotes M2 microglia/macrophages polarization. We suggest that neuropathic pain therapies should be shifted from blanketed microglia/macrophage suppression toward maintenance of the balance between neuroprotective and neurotoxic microglia/macrophage phenotypes.